Analyzing Social Media as Career Education Source : Case in Tiktok Account @vmuliana - Auliya Mutmainnah; Amalia Azahra Putri; Dinda Vania Maheswari; Yonga Eky Ramadhan; Fatma Dian Pratiwi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
Social media can be used by communities for a variety of needs, one of which is a means of employment. TikTok is one of the social media that currently abounds in search of information about career. The TikTok account owned by Vina Muliana, @vmuliana introduced education carrier that could help his followers to find job. The study uses the Stuart Hall's reception theory aimed at analyzing the followers' reception and the effects of the content education career of TikTok account @vmuliana as dominant hegemonic position, negotiated position, dan oppositional position. The result of this study indicates that followers have receptions and differing effects on career education content on @vmuliana's video feature, like and comments, and the hashtag on TikTok. There are twenty-two decoding messages dominant hegemonic, two negotiated position, and three oppositional positions. The majority of the informers responded favourably to content on @vmuliana's TikTok account since the informants were helped by the information given from their experience. In general, the informant agrees with the video content on TikTok @vmuliana's account is very informative and helpful, but some consider it not to be impacted on a career. Informants as followers to TikTok account @vmuliana consider that there is a less appropriate feature in some of the content it contains.Keywords: reception analysis, career education, TikTok, @vmuliana